Development of in vitro produced bovine embryos in four different culture media - DOGAN, IBRAHIM; SAGIRKAYA, HAKAN; SOYLU, M KEMAL; NUR, ZEKARIYA; YERLIKAYA, HUSEYIN (The Indian Journal of Animal Sciences, 2014)
The objective of this study was to compare the developmentai ability of embryos in 4 different media, CR I aa, modified CR2, BCEM-g and TCM-199. Bovine oocytes were matured and then fertilized in vitro. A total of 915 oocytes = were used for fertilizatiqn, 681 (74%) of which cleaved, The 2-cell embryos were divided into 4 groups, and cultured in 1 of the 4 different culture media. Percentage of development to morula-blastocyst stage from the 2 cell stage were determined as 46. 31,30 and 28% for CRI aa, CR2, BCEM-g and TCM-I99 culture media respectively. The development rate obtained with CR I aa was significantly’higher (P<0.01) compared to that with the other media.